Drug-Eluting Stent (DES) Induced Coronary Artery Aneurysm - A Case Report - Choudhury, Amal Kumar; Akhtaruzzaman, M; Khalequzzaman, M; Hasem, S; Choudhury, TA; Sharafat, NI (Cardiovascular Journal, 2013)
Drug-eluting stents (DES), which locally elute antiproliferative drugs, can dramatically inhibit neointimal growth. However, several pathological studies have indicated that DES may delay healing after vascular injury, and DES implantation may be theoretically associated with a risk of coronary artery aneurysm formation. Coronary aneurysms have been reported from 3 days to up to 4 years after DES implantation procedures, with varying clinical presentations. Mr. X, 60 years old diabetic, hypertensive got admitted in NICVD and was diagnosed as a case of Chronic Stable Angina. His ETT was strongly positive, CAG showed significant long lesion in LAD. Direct stenting with DES to LAD done and whole procedure was uneventful. After 10 days of PCI patient got readmitted in hospital with complaints of chest discomfort with high grade fever for 2 days. ECG showed AMI (Extensive Anterior) indicating involvement of LAD territory with strong suspicion of Sub Acute Stent Thrombosis (SAST). Streptokinase could not be given due to delayed arrival. Patient was treated conservatively with Low Molecular Weight Heparin. Check CAG was done 7 days after readmission showing Patent stent in LAD with aneurysmal dilatation at the distal end of stent in LAD. The objective of this case report is to focus on the rare but not uncommon incidence of stent implantation. Cardiovascular Journal Volume 6, No. 1, 2013, Page 63-67 DOI: http://dx.doi.org/10.3329/cardio.v6i1.16118